Preparation method of anionic coupling eutectic gel composite electrolyte
By adopting anion coupling strategy and porous covalent organic frame materials in eutectic gel composite electrolytes, the problem of inhibiting lithium ion conduction by anions is solved, and high lithium ion conductivity and stable battery cycling performance are achieved.
Patent Information
- Application Number
- CN202411950574.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The inhibition of lithium ion conduction by anions in eutectic gel composite electrolytes leads to a low ion conductivity, which limits its application in actual batteries.
Anion coupling strategy is adopted, and anionic coupling eutectic gel composite electrolyte is combined with polymer materials using a structurally adjustable porous covalent organic framework (COF) material. The pore size and polar functional groups of COF materials can effectively adsorb anion aggregates and reduce the conduction resistance of lithium ions.
It significantly improves the migration ability and conductivity of lithium ions, improves the interface compatibility of lithium metal, and improves the cycle stability of solid-state batteries and the overall performance of the battery.
Smart Images

Figure CN119812453A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer solid electrolytes, and in particular relates to a preparation method for improving the lithium ion conductivity of a eutectic gel composite electrolyte through an anion coupling strategy. Background Art
[0002] As the global demand for clean energy continues to grow, lithium-ion batteries play an increasingly important role in the field of energy storage. However, traditional liquid electrolytes have exposed many problems in high energy density and large-scale applications, such as flammability, thermal runaway risks, and poor long-cycle stability. Therefore, the development of high-performance solid electrolytes has become an important way to solve these problems. Solid electrolytes can not only effectively improve the safety of batteries, but also improve the energy density and cycle life of batteries.
[0003] In the research of solid electrolytes, polymer solid electrolytes have attracted much attention due to their excellent flexibility and process adaptability. However, existing polymer electrolytes have the problem of low ionic conductivity, especially at room temperature, which limits their application in practical batteries. In order to overcome this technical bottleneck, researchers have tried to improve the performance of polymer solid electrolytes by introducing highly conductive inorganic fillers or designing composite structures with ion conduction functions. Among them, eutectic-based gel composite electrolytes are considered to be a solution with great potential.
[0004] Eutectic gel composite electrolytes can achieve both high ionic conductivity and good mechanical stability by combining polymers, eutectic materials and liquid electrolytes. However, in the eutectic system, the strong interaction between solvated lithium ions and anions will lead to obstructed lithium ion transport, thereby limiting the overall ionic conductivity of the composite electrolyte. This limitation mainly comes from the formation of anion aggregates, which hinder the migration path of free lithium ions and reduce the conduction efficiency of lithium ions in the electrolyte. Therefore, how to effectively regulate the anion aggregation phenomenon and release more mobile lithium ions is one of the key challenges in the research of eutectic gel composite electrolytes.
[0005] In response to this problem, researchers have proposed a strategy to modify ionic ceramic conductor materials as fillers to enhance the solvation and transport capabilities of lithium ions; or to regulate ion distribution by changing the microstructural characteristics of the polymer matrix through chemical modification; or to construct ion channels of polymer composite electrolytes by introducing porous materials. For example, our previous report "A method for preparing a eutectic gel composite electrolyte membrane with a high lithium ion migration number, CN202210875952.2" greatly improved the lithium ion migration number, but the problem of incompatibility between the ionic ceramic conductor and the PVDF-based polymer interface is still prominent. In addition, this method still has the shortcomings of large amount of ceramic conductor and uneven dispersion. The patent "A method for preparing a zwitterionic modified PVDF polymer electrolyte, CN202410984911.6" reported by Xiong Jie et al. significantly improved the ionic conductivity and polymer structural stability of the polymer electrolyte. However, the zwitterionic material of propane sulfonate pyridinium salt may degrade or degrade under charge and discharge conditions, thereby affecting the long-term stability of the electrolyte and the battery cycle life, increasing the uncontrollable risk of battery safety. The patent "A solid electrolyte composite membrane and its preparation method and application, CN202410301369.X" published by Li Yongli et al. uses a porous metal organic framework (MOFs) material and a polymer composite to construct a solid electrolyte composite membrane. However, MOFs materials have challenges such as insufficient stability of structural destruction during the charging and discharging process, and the MOFs preparation process is complex and the raw materials are expensive.
[0006] Porous covalent organic framework (COF) is an ideal choice due to its unique polar structure, large specific surface area and high chemical stability. The porous polar framework of COF material can effectively adsorb anion aggregates, thereby reducing the effect of anions on lithium ion migration. Studies have reported the use of inorganic materials such as porous silica and zeolite to adsorb anions in the electrolyte, thereby improving the efficiency of lithium ion migration. However, these inorganic materials have certain limitations in flexible design and interface stability. COF materials show greater potential in this field due to their designability and diversity. By regulating the pore size, surface chemical properties and polar characteristics of COF, its adsorption capacity for anions can be further optimized. For example, during the preparation process, anions (such as halide ions, sulfate ions, etc.) are combined with these functional groups through chemical bonds or coordination bonds to form stable anion conjugates, which further form a more efficient and stable composite system with the polymer matrix. In addition, the ordered structure and good chemical stability of COF materials also make it exhibit excellent stability and durability during long cycles, which can meet the needs of practical applications. Summary of the invention
[0007] The purpose of the present invention is to solve the problem of the inhibition of lithium ion conduction by anions in the above-mentioned eutectic gel composite electrolyte, and propose a method for preparing an anion-coupled eutectic gel composite electrolyte. The present invention uses a structurally adjustable COF material for anion coupling, which can significantly improve the migration ability of lithium ions and improve the lithium metal interface compatibility.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] An anion-coupled eutectic gel composite electrolyte comprises 85-93 wt% of a composite electrolyte and 7-15 wt% of a residual solvent, wherein the residual solvent is coupled in the composite electrolyte material in the form of a eutectic solvent;
[0010] The composite electrolyte material includes a one-dimensional porous covalent organic framework material and a polymer material in a mass ratio of 1: (8-15), wherein the pore size of the one-dimensional porous covalent organic framework material is 2-4 nanometers and the specific surface area is 1300-1600m 2 / g, with thiol (-SH) and amine (-NH2) polar functional groups on the surface;
[0011] The anion-coupled eutectic gel composite electrolyte has a thickness of 30 to 60 microns and does not contain any fluid liquid.
[0012] Furthermore, the one-dimensional porous covalent organic framework material is prepared by the following steps:
[0013] (1) adding 1,3,5-benzenetricarboxaldehyde to a mixed solvent of acetonitrile and water, and mixing by ultrasonication to obtain a mixed solution A; wherein the mass concentration of 1,3,5-benzenetricarboxaldehyde in the mixed solution A is 1 to 3 mg / mL;
[0014] (2) adding 2,5-diamino-1,4-benzenedithiol dihydrochloride to deionized water, stirring at a speed of 300 to 600 r / min for 0.5 to 1 hour to obtain a mixed solution B; wherein the mass concentration of 2,5-diamino-1,4-benzenedithiol dihydrochloride in the mixed solution B is 3 to 7 mg / mL;
[0015] (3) Mixing the mixed solution A and the mixed solution B in a volume ratio of 1:1 to obtain a mixed solution C; adding glacial acetic acid as a catalyst to the mixed solution C by dropping and stirring, the stirring speed is controlled at 100 to 300 r / min, the stirring time is 20 to 60 min, and after the stirring is completed, the mixture is allowed to stand at room temperature for 24 to 96 hours, and the precipitate is washed 2 to 6 times by centrifugation with ethanol; and vacuum drying is performed in a vacuum environment at a temperature of 60 to 100° C. for 1 to 2 hours to obtain a one-dimensional porous covalent organic framework material.
[0016] Furthermore, the polymer is polyvinylidene fluoride-chlorotrifluoroethylene.
[0017] Furthermore, the residual solvent is one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, and acetonitrile, or a mixture of two or more thereof.
[0018] A method for preparing an anion coupled eutectic gel composite electrolyte comprises the following steps:
[0019] S1. Raw material pretreatment:
[0020] The polyvinylidene fluoride-chlorotrifluoroethylene, 1,3,5-triscarboxaldehyde ligand, 2,5-diamino-1,4-benzenedithiol dihydrochloride ligand and lithium salt are vacuum dried at 40°C to 100°C for 0.5h to 4h;
[0021] S2.COF polar powder preparation:
[0022] 2.1 Add the 1,3,5-benzenetricarboxaldehyde treated with S1 into a mixed solvent of acetonitrile and water, and mix them evenly by ultrasonication to obtain a mixed solution A; wherein the mass concentration of 1,3,5-benzenetricarboxaldehyde in the mixed solution A is 1-3 mg / mL;
[0023] 2.2 Add the 2,5-diamino-1,4-benzenedithiol dihydrochloride treated with S1 into deionized water, and stir at a speed of 300-600 r / min for 0.5-1 hour to obtain a mixed solution B; wherein the mass concentration of 2,5-diamino-1,4-benzenedithiol dihydrochloride in the mixed solution B is 3-7 mg / mL;
[0024] 2.3 Mix the mixed solution A and the mixed solution B in a volume ratio of 1:1 to obtain a mixed solution C; add glacial acetic acid as a catalyst to the mixed solution C by dropping and stirring, the stirring speed is controlled at 100-300 r / min, the stirring time is 20-60 min, after the stirring is completed, the reaction is allowed to stand at room temperature for 24-96 hours, and the precipitate is washed 2-6 times by centrifugation with ethanol; vacuum drying is performed in a vacuum environment at a temperature of 60-100° C. for 1-2 hours to obtain COF polar powder;
[0025] S3. Lithium salt / polymer slurry preparation:
[0026] Add the lithium salt treated with S1 to the mixed solvent, heat and stir in a water bath at 40-80°C, with a stirring speed of 300-600 r / min, until it is fully dissolved and evenly dispersed; then add the polyvinylidene fluoride-trifluorochloroethylene polymer treated with S1, and continue to stir at a uniform speed for 2h-6h to form an ionic sol; during the stirring process, perform ultrasonic debubbling treatment for 2-3 times for 5min-30min continuously;
[0027] S4.COF / lithium salt / polymer slurry preparation:
[0028] Weigh the COF polar powder obtained in S2, and add it to the ionic sol obtained in S3 in 3 batches. Stir for 30 minutes after adding each batch of COF polar powder. Stir for 2 to 4 hours after adding COF for the last time to obtain a COF / lithium salt / polymer mixed slurry.
[0029] S5. Preparation of anion-coupled eutectic gel composite electrolyte:
[0030] The mixed slurry obtained by S4 is coated on the substrate by spin coating, and allowed to stand for 12h to 48h to allow the solvent to evaporate slowly and evenly to obtain a wet gel film, and the spin coating speed is 200r / min to 600r / min; then it is vacuum dried at 60℃ to 100℃ for 24h to 72h to obtain an anion-coupled eutectic gel composite electrolyte membrane.
[0031] Preferably, in the polyvinylidene fluoride-chlorotrifluoroethylene P (VDF-CTFE) in step S1, the proportion of CTFE branches is between 6% and 25%; the purity of 1,3,5-benzene trimesaldehyde ligand and 2,5-diamino-1,4-benzenedithiol dihydrochloride ligand reaches more than 99.9%.
[0032] Preferably, the lithium salt in step S1 is at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(catechol)borate, and lithium (fluorosulfonyl)trifluoromethylsulfonylimide.
[0033] Preferably, in step 2.1, in the mixed solvent of acetonitrile and water, the volume ratio of acetonitrile to water is 1:(0.2-0.6), preferably 1:0.3; in step 2.3, the volume ratio of the added glacial acetic acid to the mixed solution C is (1-4):20, preferably 3:20.
[0034] Preferably, the mixed solvent in step S3 is one or a mixture of two or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, and acetonitrile.
[0035] Preferably, in the ionic sol prepared in step S3, the mass ratio of the polymer is 5-20wt%. In step S3, the mass ratio of the added polymer to the lithium salt is (2-4):1.
[0036] Preferably, in step S4, the mass ratio of the weighed COF polar powder to the polymer in the ionic sol is 1:(8-15).
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The invention provides a method for preparing an anion-coupled eutectic gel composite electrolyte. The covalent organic framework material is prepared by a simple method, and high temperature, high pressure and long reaction conditions are not required. Only stirring, catalysis and static reaction at room temperature are required to obtain a one-dimensional porous covalent organic framework material. The prepared porous covalent organic framework material has abundant thiol (-SH) and amine (-NH2) polar functional groups, which can couple anions, residual solvents and other anion aggregates in the composite electrolyte, reduce lithium ion conduction resistance, and achieve high room temperature lithium ion conductivity (0.08-0.6mS cm) of the eutectic gel composite electrolyte. -1 ) and high ion migration number (0.24-0.5). In addition, thanks to the strong adsorption of thiol (-SH) and amine (-NH2), the prepared eutectic gel composite electrolyte has good interfacial compatibility with the positive and negative electrodes of solid-state batteries, and the assembled high positive electrode loading (8 mg cm -2 ) can stably cycle 200 times at 0.5C current density at room temperature, significantly improving the cycle stability of solid-state batteries. Therefore, the preparation method of the eutectic gel composite electrolyte membrane has the advantages of simple preparation conditions, superior electrolyte performance, and good interface performance, and has great potential for large-scale production and industrialization in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A flow chart of a method for preparing an anion-coupled eutectic gel composite electrolyte provided by the present invention;
[0040] Figure 2 This is an optical image of the COF polar powder obtained in step S2 of Example 1;
[0041] Figure 3 This is a Raman spectrum image of the COF polar powder obtained in step S2 of Example 1;
[0042] Figure 4 The DC polarization curve of the anion-coupled eutectic gel composite electrolyte prepared in Example 1;
[0043] Figure 5 The AC impedance test diagram of the anion-coupled eutectic gel composite electrolyte prepared in Example 1 before and after the DC polarization test;
[0044] Figure 6 This is a test graph of the ionic conductivity of the anion-coupled eutectic gel composite electrolyte prepared in Example 1;
[0045] Figure 7 This is a solid-state battery cycle performance test diagram of the anion-coupled eutectic gel composite electrolyte prepared in Example 1. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments:
[0047] Example 1
[0048] A method for preparing an anion coupled eutectic gel composite electrolyte comprises the following steps:
[0049] S1. Raw material processing: the polyvinylidene fluoride-trifluorochloroethylene, trimesic acid ligand, 2,5-diamino-1,4-benzenedithiol dihydrochloride ligand and lithium salt raw materials are vacuum dried at 40°C for 0.5h; wherein, in the polyvinylidene fluoride-trifluorochloroethylene, the proportion of trifluorochloroethylene side chains is 10%.
[0050] S2, COF polar powder preparation: Measure 10mL of a mixed solution of acetonitrile and water of 1,3,5-benzene trimeraldehyde with a mass concentration of 2mg / mL, stir thoroughly, and set aside after ultrasonic treatment. Weigh 10mL of a deionized water solution of 2,5-diamino-1,4-benzenedithiophenol dihydrochloride with a mass concentration of 4mg / mL, control the stirring speed at 300r / min, and stir for 0.5h before use. After mixing the two solutions, add 3mL of glacial acetic acid as a catalyst, and stir while adding the catalyst. The stirring speed is controlled at 120r / min, and the stirring time is 30min. After stirring, stand the reaction at room temperature for 24 hours, centrifuge and wash the precipitate twice with ethanol, and then vacuum dry it at 60°C for 1 hour to obtain COF polar powder.
[0051] S3, preparation of lithium salt / polymer slurry: adding the lithium salt obtained in step S1 to the mixed solvent under water bath heating conditions and stirring, the water bath temperature is 60°C, the stirring speed is 400r / min, until it is fully dissolved and evenly dispersed; then adding polyvinylidene fluoride-chlorotrifluoroethylene polymer, stirring at a constant speed for 3 hours to form an ionic sol. During the stirring process, ultrasonic debubbling treatment is continuously performed twice for 20 minutes.
[0052] S4, COF / lithium salt / polymer slurry preparation: Weigh the COF polar powder obtained in step S2, and add it to the ionic sol obtained in step S3 in 3 batches, and stir each batch of COF polar powder for 30 minutes. Stir for 2 hours after the last addition of COF to obtain COF / lithium salt / polymer mixed slurry.
[0053] S5. Preparation of anion-coupled eutectic gel composite electrolyte: Take 3 mL of the mixed slurry obtained in step S4 and drop it on a clean and flat glass plate, spin coat it at a rotation speed of 300 r / min to evenly coat it on the substrate, let it stand for 12h-48h to allow the solvent to evaporate slowly and evenly to obtain a wet gel film, and then vacuum dry it at 60°C for 48h to obtain anion-coupled eutectic gel composite electrolyte membrane.
[0054] Example 2
[0055] The difference between Example 2 and Example 1 is that: in step S1, the vacuum drying temperature is 60° C., the vacuum drying time is adjusted to 1 hour, and the proportion of trifluoroethylene side chains in polyvinylidene fluoride-trifluoroethylene is 8%. The remaining steps are exactly the same as in Example 1.
[0056] Example 3
[0057] Compared with Example 2, Example 3 differs in that: in step S1, the vacuum drying temperature is 80° C., the vacuum drying time is adjusted to 4 hours, and the proportion of trifluoroethylene side chains in polyvinylidene fluoride-trifluoroethylene is 16%. The remaining steps are exactly the same as Example 2.
[0058] Example 4
[0059] Compared with Example 3, Example 4 differs in that: in step S1, the vacuum drying temperature is 60° C., the vacuum drying time is adjusted to 4 h, the amount of glacial acetic acid catalyst is 2 mL, the room temperature standing reaction time is 36 h, the number of centrifugal washing is 4 times, and the vacuum drying temperature is 60° C. The remaining steps are exactly the same as those in Example 3.
[0060] Example 5
[0061] Compared with Example 4, Example 5 differs in that: in step S3, the mixed solvent is N,N-dimethylacetamide and dimethyl sulfoxide in a volume ratio of 3:1, and the mass ratio of the added polymer and lithium salt is 4:1. The remaining steps are exactly the same as those of Example 4.
[0062] Example 6
[0063] Compared with Example 5, Example 6 differs in that: in step S3, the mixed solvent is N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone in a volume ratio of 1:1:1, and the mass ratio of the added polymer and lithium salt is 3:1. The remaining steps are exactly the same as those in Example 5.
[0064] Example 7
[0065] The difference between Example 7 and Example 6 is that in step S4, the amount of COF is adjusted to 0.01 g. The remaining steps are exactly the same as those in Example 6.
[0066] Example 8
[0067] The difference between Example 8 and Example 7 is that in step S5, 4 mL of the mixed slurry obtained in step S3 is dropped onto a clean and flat glass plate, left to stand for 24 hours to evaporate the solvent, and then vacuum dried at 60° C. for 48 hours. The remaining steps are exactly the same as those in Example 7.
[0068] Example 9
[0069] The difference between Example 9 and Example 8 is that in step S5, 5 mL of the mixed slurry obtained in step S3 is dropped onto a clean and flat glass plate, spin-coated at a rotation speed of 400 r / min, left to stand for 36 hours to volatilize the solvent, and then vacuum dried at 80° C. for 60 hours. The remaining steps are exactly the same as those of Example 8.
[0070] Example 10
[0071] The difference between Example 10 and Example 9 is that in step S5, the rotation speed of the spin coater is 600 r / min, the solvent volatilization time is 48 h, the vacuum drying temperature is 100° C., and the drying time is 72 h. The remaining steps are exactly the same as those of Example 9.
[0072] The following table is a performance comparison information of Example 1 to Example 10:
[0073]
[0074] In summary, the present invention provides a method for preparing an anion-coupled eutectic gel composite electrolyte. The pore size and distribution of anion-coupled polar functionalized COF materials with rich pores can be further optimized to meet the conduction requirements of specific ions; the anion-coupled polar functionalized COF can be prepared in large quantities under room temperature conditions, which is energy-saving and environmentally friendly; the functional groups such as thiol (-SH) and amine (-NH2) on the surface of the material not only enhance the chemical activity of the material, but also improve the interface compatibility of the eutectic gel composite electrolyte with the lithium metal negative electrode and the positive electrode material, thereby significantly improving the cycle stability of the battery.
[0075] Based on the above invention information, those skilled in the art will appreciate that the embodiments described herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such special statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.
Claims
1. An anion coupled eutectic gel composite electrolyte, characterized in that: The composite electrolyte comprises 85-93 wt% of a composite electrolyte and 7-15 wt% of a solvent, wherein the solvent is coupled in the composite electrolyte material in the form of a eutectic solvent; The composite electrolyte material includes a one-dimensional porous covalent organic framework material and a polymer material in a mass ratio of 1: (8-15), wherein the pore size of the one-dimensional porous covalent organic framework material is 2-4 nanometers and the specific surface area is 1300-1600m 2 / g, and has thiol and amine polar functional groups on the surface.
2. The anion-coupled eutectic gel composite electrolyte according to claim 1, characterized in that: The one-dimensional porous covalent organic framework material is prepared by the following steps: (1) adding 1,3,5-benzenetricarboxaldehyde to a mixed solvent of acetonitrile and water, and mixing by ultrasonication to obtain a mixed solution A; wherein the mass concentration of 1,3,5-benzenetricarboxaldehyde in the mixed solution A is 1 to 3 mg / mL; (2) adding 2,5-diamino-1,4-benzenedithiol dihydrochloride to deionized water, stirring and mixing to obtain a mixed solution B; wherein the mass concentration of 2,5-diamino-1,4-benzenedithiol dihydrochloride in the mixed solution B is 3 to 7 mg / mL; (3) Mixing the mixed solution A and the mixed solution B in a volume ratio of 1:1 to obtain a mixed solution C; adding glacial acetic acid as a catalyst to the mixed solution C, stirring, standing for reaction, and centrifuging to obtain a product; and drying the obtained product in a vacuum environment at a temperature of 60 to 100° C. to obtain a one-dimensional porous covalent organic framework material.
3. A method for preparing an anion coupled eutectic gel composite electrolyte, characterized in that: The following steps are involved: S1. Raw material pretreatment: The polyvinylidene fluoride-chlorotrifluoroethylene, 1,3,5-triscarboxaldehyde ligand, 2,5-diamino-1,4-benzenedithiol dihydrochloride ligand and lithium salt are vacuum dried at 40°C to 100°C for 0.5h to 4h; S2.COF polar powder preparation: 2.1 Add the 1,3,5-benzenetricarboxaldehyde treated with S1 into a mixed solvent of acetonitrile and water, and mix them evenly by ultrasonication to obtain a mixed solution A; wherein the mass concentration of 1,3,5-benzenetricarboxaldehyde in the mixed solution A is 1-3 mg / mL; 2.2 Add the 2,5-diamino-1,4-benzenedithiol dihydrochloride treated with S1 into deionized water, stir and mix evenly to obtain a mixed solution B; wherein the mass concentration of 2,5-diamino-1,4-benzenedithiol dihydrochloride in the mixed solution B is 3-7 mg / mL; 2.3 Mix the mixed solution A and the mixed solution B in a volume ratio of 1:1 to obtain a mixed solution C; add glacial acetic acid as a catalyst to the mixed solution C, stir, stand for reaction, and centrifuge to obtain a product; dry the obtained product in a vacuum environment at a temperature of 60 to 100° C. to obtain COF polar powder; S3. Lithium salt / polymer slurry preparation: The lithium salt treated with S1 is added to the mixed solvent and stirred in a water bath at 40-80°C until it is fully dissolved and evenly dispersed; then the polyvinylidene fluoride-chlorotrifluoroethylene polymer treated with S1 is added and stirred to form an ionic sol; S4.COF / lithium salt / polymer slurry preparation: Weigh the COF polar powder obtained in S2, and add it to the ionic sol obtained in S3 in 3 batches. Stir for 30 minutes after adding each batch of COF polar powder. Stir for 2 to 4 hours after adding COF for the last time to obtain a COF / lithium salt / polymer mixed slurry. S5. Preparation of anion-coupled eutectic gel composite electrolyte: The mixed slurry obtained by S4 is coated on a substrate by a spin coating method and allowed to stand to obtain a wet gel film; and then vacuum dried at 60° C. to 100° C. to obtain an anion-coupled eutectic gel composite electrolyte membrane.
4. The method for preparing the anion coupled eutectic gel composite electrolyte according to claim 3, characterized in that: In the polyvinylidene fluoride-chlorotrifluoroethylene of step S1, the proportion of chlorotrifluoroethylene side chains is 6% to 25%.
5. The method for preparing the anion coupled eutectic gel composite electrolyte according to claim 3, characterized in that: The lithium salt in step S1 is at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(catechol)borate, and lithium (fluorosulfonyl)trifluoromethylsulfonylimide.
6. The method for preparing the anion-coupled eutectic gel composite electrolyte according to claim 3, characterized in that: In step 2.1, in the mixed solvent of acetonitrile and water, the volume ratio of acetonitrile to water is 1:(0.2-0.6); in step 2.3, the volume ratio of the added glacial acetic acid to the mixed solution C is (1-4):
20.
7. The method for preparing the anion-coupled eutectic gel composite electrolyte according to claim 3, characterized in that: The mixed solvent in step S3 is one or a mixture of two or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, and acetonitrile.
8. The method for preparing the anion-coupled eutectic gel composite electrolyte according to claim 3, characterized in that: In the ionic sol prepared in step S3, the mass proportion of the polymer is 5 to 20 wt%.
9. The method for preparing the anion-coupled eutectic gel composite electrolyte according to claim 3, characterized in that: In step S3, the mass ratio of the added polymer to the lithium salt is (2-4):
1.
10. The method for preparing the anion coupled eutectic gel composite electrolyte according to claim 3, characterized in that: In step S4, the mass ratio of COF polar powder to polymer is 1:(8-15).
Citation Information
Patent Citations
Preparation method of eutectic gel composite electrolyte membrane with high lithium ion transference number
CN115101805A
Covalent organic framework-based semi-solid electrolyte composite diaphragm as well as preparation method and application thereof
CN115312966A
Preparation method, product and application of poly oxime ester gel polymer electrolyte
CN115579516A
Preparation method of covalent organic framework enhanced gel electrolyte for lithium-sulfur battery
CN116845352A
Preparation and application of flame-retardant composite gel electrolyte with high sodium ion selectivity
CN117154204A